Time of Death Relative to Alcohol Use: Application of Brain: blood Ratios and Gastric Ethanol - John Brick (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2016)
Ethyl alcohol (alcohol) is the most commonly analyzed toxin in forensic laboratories, the drug most often found postmortem, regardless of the cause of death and the drug most frequently reported in violent deaths [1,2]. Death from alcohol poisoning is commonly reported [2,3] and depending on the year of the study, alcohol intoxication is found in 40 percent of all highway fatalities, 47 percent of drowning deaths and up to 77 percent of fatal fall-down injuries in the United States [4]. Criminal investigation is often initiated in death cases in order to relate the degree of impairment just before a fatality to the ability to operate a vehicle, exercise good judgment, etc. Often, civil litigation requires that blood, other fl uids or tissues obtained post-mortem be evaluated to further understand the pattern of drinking and intoxication prior to death. In such cases, the level of blood or brain alcohol in the decedent driver, pedestrian or other victims may be useful in understanding the role of alcohol as a contributing factor to a fatal event. Forensic evidence may also be important in dram-shop or social host liability litigation, where the estate of a decedent driver or passenger brings civil suit against a bar, alleging that the decedent was served while visibly intoxicated. In such cases, the interpretation of alcohol in blood, brain or other fluids or tissues may be useful in answering questions relating the effects of alcohol intoxication to behavior.